Horizontal profile of a moving red line cusp aurora. Issue 3 (7th March 2017) - Taguchi, S.; Chiba, Y.; Hosokawa, K.; Ogawa, Y.
Abstract: Auroral emission at a wavelength of 630.0 nm (red line) has a long radiative time. In this study, we show how this long radiative time controls the horizontal extent of a moving mesoscale aurora, which is typical of the cusp. Using high time resolution (4 s) observations by an all‐sky imager at Longyearbyen, Svalbard, and observations by the European Incoherent Scatter Svalbard Radar (ESR), we examined the auroral emission enhancements obtained in the cusp during an interval of southward interplanetary magnetic field on 27 November 2011. Simultaneous observations from the all‐sky imager and the ESR clearly show the manner in which auroral emission regions passed through the radar's field of view. When the front edge of the moving auroral structure intersected the radar's field of view, the ESR electron temperature was enhanced. A few minutes later, the ESR electron temperature dropped to the background level, indicating that the mesoscale electron precipitation region shifted away from the radar's field of view. At that time, the auroral emission in the radar's field of view decreased but still had adequate intensities. These results provide evidence demonstrating that moving cusp auroral emission occurs behind the electron precipitation region as well as inside that region. We interpreted this feature semiquantitatively by using the equation of continuity of the density of the excited atomic oxygen. Our model indicates that the maximum intensity in the moving auroral structure occurs at a point along the trailing edge of the electron precipitation region and that the velocity of that region is important for determining how the 630.0 nm aurora emissions extend horizontally. Key Points: A semiquantitative model explains the intensity variation of a moving red line cusp aurora A moving red line cusp aurora does not have electron precipitation in its rear half The velocity of the electron precipitation region is important for determining how the red line aurora extends horizontally